Detection of translational noncrystallographic symmetry in Patterson functions. Issue 2 (8th February 2021) - Caballero, Iracema; Sammito, Massimo D.; Afonine, Pavel V.; Usón, Isabel; Read, Randy J.; McCoy, Airlie J.
Abstract : Translational noncrystallographic symmetry (TNCS) was analysed using a curated database of 80 000 protein structures to inform an algorithm for the detection of TNCS order. Abstract : Detection of translational noncrystallographic symmetry (TNCS) can be critical for success in crystallographic phasing, particularly when molecular‐replacement models are poor or anomalous phasing information is weak. If the correct TNCS is detected then expected intensity factors for each reflection can be refined, so that the maximum‐likelihood functions underlying molecular replacement and single‐wavelength anomalous dispersion use appropriate structure‐factor normalization and variance terms. Here, an analysis of a curated database of protein structures from the Protein Data Bank to investigate how TNCS manifests in the Patterson function is described. These studies informed an algorithm for the detection of TNCS, which includes a method for detecting the number of vectors involved in any commensurate modulation (the TNCS order). The algorithm generates a ranked list of possible TNCS associations in the asymmetric unit for exploration during structure solution.